The GTPase Activity of Escherichia coli FtsZ Determines the Magnitude of the FtsZ Polymer Bundling by ZapA in Vitro - Mohammadi, Tamimount (American Chemical Society, 2009)
[Image: see text] FtsZ polymerizes in a ring-like structure at mid cell to initiate cell division in Escherichia coli. The ring is stabilized by a number of proteins among which the widely conserved ZapA protein. Using antibodies against ZapA, we found surprisingly that the cellular concentration of ZapA is approximately equal to that of FtsZ. This raised the question of how the cell can prevent their interaction and thereby the premature stabilization of FtsZ protofilaments in nondividing cells. Therefore, we studied the FtsZ−ZapA interaction at the physiological pH of 7.5 instead of pH 6.5 (the optimal pH for FtsZ polymerization), under conditions that stimulate protofilament formation (5 mM MgCl(2)) and under conditions that stimulate and stabilize protofilaments (10 mM MgCl(2)). Using pelleting, light scattering, and GTPase assays, it was found that stabilization and bundling of FtsZ polymers by ZapA was inversely correlated to the GTPase activity of FtsZ. As GTP hydrolysis is the rate-limiting factor for depolymerization of FtsZ, we propose that ZapA will only enhance the cooperativity of polymer association during the transition from helical filament to mid cell ring and will not stabilize the short single protofilaments in the cytoplasm. All thus far published in vitro data on the interaction between FtsZ and ZapA have been obtained with His-ZapA. We found that in our case the presence of a His tag fused to ZapA prevented the protein to complement a ΔzapA strain in vivo and that it affected the interaction between FtsZ and ZapA in vitro.